Search for pair production of scalar top quarks in jets and missing transverse energy channel with the D0 detector - Shamim, Mansoora (Kansas State University, 2008)
This dissertation describes a search for the pair production of scalar top quarks, tilde[subscript] 1, using a luminosity of 995 pb[superscript-1] of data collected in p[bar over]p collisions with the D0 detector at the Fermilab Tevatron Collider at a center-of-mass energy sqrt[s] = 1.96 TeV. Both scalar top quarks are assumed to decay into a charm quark and a neutralino, [tilde chi superscript 0 subscript 1]where [(tilde chi superscript 0 subscript 1)]is the lightest supersymmetric particle. This leads to a final state with two acoplanar charm jets and missing transverse energy. The yield of such events in data is found to be consistent with the expectations from known standard model processes. Sets of tilde [subscript 1] and tilde chi [superscript 0 subscript 1] masses are excluded at the 95% confidence level that substantially extend the domain excluded by previous searches. With the theoretical uncertainty on the pair production cross section taken into account, the largest limit for m[subscript tilde subscript 1] is m[subscript tilde chi subscript 1> 150 GeV, for m [subscript tilde chi negative 0 subscript 1]= 65 GeV.
Keywords: Supersymmetirc top quark; Physics, Elementary Particles and High Energy (0798)